1992
DOI: 10.1007/bf01204110
|View full text |Cite
|
Sign up to set email alerts
|

Motives for parenthood and response to failed in vitro fertilization: Implications for counseling

Abstract: The purpose of this investigation was to identify in vitro fertilization (IVF) candidates' motives for parenthood and hence for seeking treatment. The relationship among identified motives, pretreatment emotional adjustment, and reaction to treatment failure was then examined. Women as a group placed greatest emphasis on fulfilling gender-role requirements, and those strongly endorsing such motives showed the poorest adjustment before IVF and the most negative reaction to first-cycle failure. In contrast, men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 14 publications
1
24
1
5
Order By: Relevance
“…Factor 3 also seems to reflect the sense of traditional parenthood (Miller, 1995), aspirations of immortality and sharing of personal values (Seaver et al, 1977) that have been part of the structure of the Childbearing Motivation Questionnaire and the Parenthood Motivation Questionnaire. On its turn, The Couple Relationship (Factor 4) refers to strengthened partnership ties or growth as a couple, being similar to relationship (Cassidy & Sintrovani, 2008) and marital completion (Newton et al, 1992) subdimensions that have been identified in prior instruments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factor 3 also seems to reflect the sense of traditional parenthood (Miller, 1995), aspirations of immortality and sharing of personal values (Seaver et al, 1977) that have been part of the structure of the Childbearing Motivation Questionnaire and the Parenthood Motivation Questionnaire. On its turn, The Couple Relationship (Factor 4) refers to strengthened partnership ties or growth as a couple, being similar to relationship (Cassidy & Sintrovani, 2008) and marital completion (Newton et al, 1992) subdimensions that have been identified in prior instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, most available instruments have been studied in samples of college students (O'Laughlin & Anderson, 2001) and pregnant or infertile couples (Bell et al, 1985;Cassidy & Sintrovani, 2008;Gauthier et al, 2007;Newton et al, 1992;Van Balen & Trimbos-Kemper, 1995). Few instruments have been studied in samples from the general population (Miller, 1995;Seaver et al, 1977), especially in the present-day context (Langdridge et al, 2005;Stöbel-Richter et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As dimensões biológicas/físicas têm sido relacionadas com a concretização de um instinto ou "apelo" do relógio biológico (Inborn & Van Balen, 2002) e a afirmação da sua fertilidade (Shover 2005) ou masculinidade/feminilidade (Newton, Hearn, Yuzpe, & Houle, 1992). O desejo de viver a gravidez e o parto (Miller, 1995) e os laços biológicos (Miller, Millstein, & Pasta, 2008) têm sido igualmente contemplados.…”
Section: Motivações Positivas Para a Parentalidadeunclassified
“…The results showed that women who participated in the group meetings (compared to the control group) showed less anxiety after IVF, however, the men who participated in the meetings (compared to the control group or those women who were undertreatment) were more optimistic and confirmed many of their irrational beliefs. Studies byTerzioglu (2001) and Newton et al (1992) on the effect of psychological and psychiatric interventions on mental disorders in infertile couples showed that psychological interventions lead to reduction of anxiety and depression in them.…”
mentioning
confidence: 99%